Fixator Mix-Nature: Experiment of Fixator Composition as a Natural Color Booster For Handmade Batik On Cotton Fabric Media - Wulandari, Tri (Institut Seni Indonesia Yogyakarta, 2022)
The natural staining process requires a fixator as a locking or reinforcing agent for colour results. The fixator materials used in general are an alum, lime, and tunjung. The natural nature of colour extract substances and the use of appropriate fixators influences the strength of natural colour results in handmade batik. This Mix-Nature Fixator experimental research combines a mixture of ingredients from alum, lime, and tunjung with a composition ratio of 1:1:1, 1:2:1, 1:3:1, - 2:1:1, 2:2:1, 2:3:1 - 3:1:1, 3:2:1, 3:3:1. The purpose of this study is to compile a table of the composition of mixed fixators of alum, lime, tunjung; to know the components of chemical elements; and to explain the success rate of Fixator Mix-Nature in the fixation process of dyeing natural colour batik on cotton fabrics. This research uses experimental methods and literature studies as the primary data collection techniques. The element test method uses the Qualitative ED-XRF test method. The practice of analyzing natural colour data results compares colour fastness test results to soap washing. The results of this experimental research are: 1) Fixator Mix-Nature table from the comparison of the composition of alum, lime, and tunjung; 2) the chemical elements in the Mix-Nature Fixator can be a unitary component of the reinforcing agent resulting from natural colours; and 3) The success rate of using the Mix-Nature Fixator that most affects the quality of natural colours is A3 Code Fixator. Code A3 Fixator results from Alum material: Chalk: Tunjung in a ratio of 1:3:1 are highly recommended as fixator substances in the fixation of natural colours.